2004
DOI: 10.1111/j.1540-8183.2004.04025.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Obstructive Sleep Apnea on FFR Measurements for Coronary Lesion Assessment

Abstract: Fractional flow reserve (FFR) determinations have been demonstrated to be largely independent of changes in systemic hemodynamic changes. Herein, we describe a case of obstructive sleep apnea cyclically altering FFR measurements from normal to abnormal in a patient with an intermediately severe coronary narrowing following treatment for an acute coronary syndrome. To eliminate uncertainty, FFR measurements should be made if possible during suspended respiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This mismatch between flow-metabolic demand coupling with OA is likely to be clinically relevant in the setting of underlying coronary artery disease, as it has recently been shown that obstructive apneas can acutely change the physiological significance of an intermediate grade coronary stenosis. 28 In this case report of a patient with obstructive sleep apnea occurring during coronary angiography, fractional flow reserve measurements varied from above to below the ischemic threshold. The presence of OSA therefore converted a functionally benign coronary lesion to a clinically significant one.…”
Section: Resultsmentioning
confidence: 86%
“…This mismatch between flow-metabolic demand coupling with OA is likely to be clinically relevant in the setting of underlying coronary artery disease, as it has recently been shown that obstructive apneas can acutely change the physiological significance of an intermediate grade coronary stenosis. 28 In this case report of a patient with obstructive sleep apnea occurring during coronary angiography, fractional flow reserve measurements varied from above to below the ischemic threshold. The presence of OSA therefore converted a functionally benign coronary lesion to a clinically significant one.…”
Section: Resultsmentioning
confidence: 86%
“…Stable hyperemia also allows pressure wire pullback recordings to assess the significance of serial lesions in the same artery by measuring the stepwise change in Pa–Pd (gradient, not FFR) as the wire is pulled back across serial stenoses . Case reports have noted that variation in Pd/Pa may occur with respiration in obstructive sleep apnea patients , but aside from such patients, Pd/Pa has been accepted as stable during adenosine infusion.…”
Section: Introductionmentioning
confidence: 99%
“…The central venous pressure, usually assumed to be negligible in most FFR calculations, is commonly elevated in patients with OSA and can cause significantly lower FFR measurements. This was illustrated as previously reported by Ciaramita et al [17]. In our case, the FFR calculation is typically performed by making an assumption of mean right atrial pressure of 5 mm Hg.…”
Section: Osa and Calculations Of Ffrmentioning
confidence: 88%
“…There has been only one report about the impact of OSA on FFR determination [17]. However, there has been no study measuring FFR and the impact on FFR measurement when treating OSA with CPAP.…”
Section: Introductionmentioning
confidence: 98%